An integrated evaluation methodology to measure ecological and economic landscape states for territorial transformation scenarios: an application in Piedmont (Italy). (October 2019) - Assumma, Vanessa; Bottero, Marta; Monaco, Roberto; Soares, Ana Jacinta
Highlights: An integrated evaluation model is proposed to assess an environmental system. A set of indicators investigates the relations between landscape ecology and landscape economics. A mathematical model evaluates the environmental system in term of states of ecological equilibrium. The model enables to identify the most valuable and the most critical areas in ecological and economic terms. The research provides a reliable support for the decision-making process Abstract: The increasing attention on environmental problems is stimulating the development of integrated evaluation approaches to territorial transformations, where different facets have to be considered. The present paper focuses on the development of a novel integrated evaluation model for measuring the ecological states and the economic values of an environmental system employing both a system of indicators and a mathematical model of Lotka-Volterra. This integrated evaluation model aims at investigating the relations between the landscape ecology and economics, and at simulating possible and future transformation scenarios for the landscape planning and management. As case study, we consider an environmental system located in Piedmont (Italy), in the Monferrato Ovadese area. The present paper proposes a suitable support for local governments to visualize outcomes and possible future scenarios, aiding the decision-making process in the definition of territorial transformation policies and actions.